(untitled) (Revista de Ciências Agroveterinárias, 2016)
The demand for blueberries has increased mainly due to the added value and the possibility of industrialization. Despite the great importance, studies are needed that focus on higher quality of seedlings and fruits, as well as appropriate plant management techniques. We studied propagation forms (micropropagation and cuttings) and pruning intensities (control, light and drastically) of blueberries ’Briteblue’. We concluded that micropropagated plants have an increased vegetative growth, as well as severe pruning provides the development of vegetative branches of greater length. Higher levels of anthocyanins were found in fruits propagated by cuttings and plants without pruning or light pruning had higher antioxidant activity.